Residential care facilities providing multidisciplinary integrated care for older people achieve higher scores on 32 risk-adjusted quality of care indicators than facilities providing usual care. Issue 2 (21st December 2011) - Cooney, Adeline; Devane, Declan
Abstract : Commentary on: Boorsma M Frijters DH Knol DL . Effects of multidisciplinary integrated care on quality of care in residential care facilities for elderly people: a cluster randomized trial. CMAJ 2011 ;183 :E724 –32 .